A Study on the Effectiveness of Integration of Music Aesthetic Education Based on "Internet Plus" into Ideological and Political Education in Universities. (12th July 2022) - Shen, Wenfang; Chen, Jianlong; Xiao, Congyong
Abstract : The high-quality development of ideological and political education in colleges and universities in the new era should focus on innovation, adherence to the concept of systematic thinking, multiparty collaborative education, accurate positioning, and promoting educational equity. On the basis of theoretical research and practical analysis, this paper examines the "current impact of music aesthetic education on college students' ideological and political education, " integrating the music aesthetic education in the "Internet + " era into all aspects of college students' ideological and political education. The teaching mode of ideological and political education has greatly improved the effectiveness of students' autonomous learning. This paper starts with investigating the current situation of ideological and political education in colleges and universities in the "Internet +" era, analyzes the necessity of integrating music aesthetic education into the research of ideological and political education in colleges and universities, and puts forward an effective and feasible way. Based on the data, this study fully explores the important role of music aesthetic education in the optimization and integration of middle school students' ideological and political education in the "Internet  + " era, and the emergence of new models. It can effectively improve the spiritual motivation and social responsibility of college students and set up correct life goals. It provides important innovative ideas and reference value for the effectiveness and substantive research of ideological and political education in colleges and universities.